IMPLEMENTING ART. 17 OF THE DSM-DIRECTIVE : PROTECTING FREEDOM OF EXPRESSION FROM THE ECONOMIC INCENTIVES OF THE ONLINE CONTENT-SHARING SERVICE PROVIDERS - Puro, Hertta (My University, 2020)
This thesis focuses on the Directive on Copyright in the Digital Single Market (EU) 2019/790 (the DSM-directive) which will be implemented into national legislations of the EU member states during 2021. The member states of the EU will be facing quite a problematic situation when implementing the DSM-directive as they should implement art. 17 without harming the freedom of expression of the internet users. In this regard, the member states should be aware of the economic incentives of the online content-sharing service providers (OCSSPs) as these incentives have great effects in relation to the freedom of expression on online platforms. Through the findings made in this thesis, I have concluded that the most essential issues between the economic incentives of the OCSSPs and freedom of expression on online platforms when implementing art. 17 are the complexity to obtain authorisations from the rightholders, the costs and efficiencies related to the filtering technologies and requirements thereof and the OCSSP incentives to create effective appeal procedures to the internet users. However, this thesis does not provide an exhaustive list of all the economic aspects which should be noted at the implementing state, but instead, it is a set of most essential elements and issues which might be problematic when implementing art. 17 of the DSM-directive. Another aim of this thesis is to provide implementation suggestions for the EU member states in order to assess the above-mentioned issues. My suggestion to tackle the authorisation issue is to make monetisation systems and copyright ownership-verification mechanisms obligatory to the OCSSPs. I also recommend strict requirements to be implied to the appeal procedures as it is clear that unnecessary content takedowns will very likely occur. However, I believe that the OCSSPs do have quite strong incentives to put up effective filtering systems without explicit requirements. Hence, I do not consider it necessary to implement strict filtering requirements to the national legislations. However, as an exception, I highly recommend making human reviewing mandatory after a specific threshold and explicitly require the OCSSPs to implement a ‘detect-and-notify’ system instead of a ‘detect-and-block’ system.
Keywords: Freedom of expression, human rights, copyright, online content-sharing service provider, OCSSP